Eliciting Looked After Children’s Views and Relationships Through Card-based Participatory Research Methods - Katherine Mycock; Sophia J Gowers (Journal of Participatory Research Methods)
This brief report discusses the usefulness of “ranking and ratings” cards in the context of participatory research with looked-after children. Within this research, we draw upon notions of participation as outlined in the UNCRC. We undertook participatory research to elicit the voices of looked after children, aged 6 to 11 years, who were involved in a school-based creative mentoring intervention. The researchers created a “ranking and ratings” card based upon the popular game “Top Trumps” to create familiarity and facilitate an examination of mentor-mentee relationships through focused conversations. We found that children’s interactions with the cards stimulated conversations which were open and detailed. This was of particular value for conducting participatory research with marginalized children who may not otherwise necessarily engage in research with an unfamiliar adult.